2022
DOI: 10.2991/ahsr.k.220106.048
|View full text |Cite
|
Sign up to set email alerts
|

Needs Analysis Development of Android-Based Physical Fitness Guide

Abstract: The purpose of this study was to analyze the needs of android-based physical fitness activity guides. This study is an exploratory, descriptive study. The subjects in the study were 80 students. The study used observation sheet intrusion and questionnaires, with data retrieval techniques through surveys. Analysis of research data uses quantitative and qualitative descriptive. The results showed a decrease in people's habits during the pandemic to move actively towards sedentary lifestyle behavior. Based on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 12 publications
0
0
0
Order By: Relevance
“…Ten question items concerning society's need for Android-based apps to measure BMI and physical fitness independently were proposed to 40 respondents. The results showed that 90% of respondents admitted the need for an app for performing physical fitness exercises (Sari et al, 2022).…”
Section: Literature Study and Information Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ten question items concerning society's need for Android-based apps to measure BMI and physical fitness independently were proposed to 40 respondents. The results showed that 90% of respondents admitted the need for an app for performing physical fitness exercises (Sari et al, 2022).…”
Section: Literature Study and Information Collectionmentioning
confidence: 99%
“…An application (hereafter referred to as "app") should hence be developed to assist them in measuring their own BMI and fitness degrees independently. Our survey, which is related to society's need analysis for the development of an Androidbased physical fitness guide, points out that 93 of the respondents prefer a fitness guide to a conventional book to do physical fitness exercises independently (Sari et al, 2022). BMI can be measured by inputting body height and weight into a determined formula, whereas the most efficient physical fitness measurement general society can perform independently is through the Rockport walking test.…”
Section: Introductionmentioning
confidence: 99%